2006
DOI: 10.1021/es060493t
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Uptake Rate Constants for Polycyclic Aromatic Hydrocarbons Accumulated by Semipermeable Membrane Devices and Triolein-Embedded Cellulose Acetate Membranes

Abstract: In this paper we report an extension of our previous work on the triolein-embedded cellulose acetate membrane (TECAM) as a passive sampling device (PSD) and describe the results from simultaneous exposure of TECAMs and triolein-containing semipermeable membrane devices (SPMDs) to PAHs in lake water for 16 days. The data obtained provided a comparison of the uptake rates of specific PAHs by the two PSDs. Using 16-day accumulation tests, similar PAH distribution patterns in TECAMs and in SPMDs (R 2 ) 0.89, p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Compared with normal adsorbents such as activated carbon and alumina, this DNA matrix showed a selective adsorptivity for the dioxin derivatives with planar structure such as dibenzo-p-dioxin, dibenzofuran, and biphenyl. Some researchers (Xu et al, 2005b;Ke et al, 2006) prepared a new type of composite membrane, triolein embedded-cellulose acetate membrane (TECAM), and used it in the uptake of six organochlorine pesticides. Results indicated that TECAM quickly and efficiently accumulated hydrophobic organochlorine pesticides (OCPs) from water.…”
Section: Biomimetic Sorbent and Its Sorption Behaviors Of Persistent mentioning
confidence: 99%
“…Compared with normal adsorbents such as activated carbon and alumina, this DNA matrix showed a selective adsorptivity for the dioxin derivatives with planar structure such as dibenzo-p-dioxin, dibenzofuran, and biphenyl. Some researchers (Xu et al, 2005b;Ke et al, 2006) prepared a new type of composite membrane, triolein embedded-cellulose acetate membrane (TECAM), and used it in the uptake of six organochlorine pesticides. Results indicated that TECAM quickly and efficiently accumulated hydrophobic organochlorine pesticides (OCPs) from water.…”
Section: Biomimetic Sorbent and Its Sorption Behaviors Of Persistent mentioning
confidence: 99%
“…This indicates that TECAM sampling rates can be expected to decrease for some higher molecular weight OCPs. Indeed, our early results have also revealed that the k u s of PAHs decreased when logK ow exceeded approximately 6.0 [12].…”
Section: Determination Of Uptake Kinetic Parametersmentioning
confidence: 72%
“…Recently a novel membrane-based extraction technique was developed in our laboratory for in situ passive sampling of waterborne hydrophobic organic pollutants involving triolein-embedded cellulose acetate membrane (TECAM) [11,12]. In TECAM, the triolein drops embed in the matrix of cellulose acetate polymers and closely adhere with the polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semipermeable membrane devices (SPMD), which are based on the diffusion of hydrophobic substances from water to membrane bags filled with lipophilic phases, are widely used for monitoring organic contaminants in water (Huckins et al, 1990;Frank, 2005). It has also been reported that triolein embedded cellulose acetate (CA) membrane could quickly and efficiently accumulate hydrophobic POPs from water (Xu et al, 2005;Ke et al, 2006). In the present study, a novel composite absorbent containing the lipid triolein was designed using the concept of bioaccumulation and was used to remove trace level lipophilic organics from water.…”
Section: Introductionmentioning
confidence: 95%